2020
DOI: 10.1177/1098214020908211
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intuition in Evaluative Judgment and Decision

Abstract: Expert intuition is increasingly considered to be a valid form of knowledge, and research has proven its effectiveness in judgment and decision making in various fields. Theorists seem to recognize the contributions of intuition within evaluative practice, but it has never been well-documented. This article presents a study on expert intuition, addressing the manner in which intuition is developed, as well as how it contributes to producing judgments in the specific context of program evaluation. In-depth, in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…Our findings are consistent with this concept in that we found that development of the clinical gaze is a constant process that requires time and opportunities for reflection in daily work. Our findings are also consistent with the findings of Hurteau et al ( 2020 ) that the development of intuition is fostered by expertise and experiences. Also consistent with the findings of Kvande et al ( 2016 ), our study emphasizes the importance of being physically present with a patient to develop the clinical gaze.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with this concept in that we found that development of the clinical gaze is a constant process that requires time and opportunities for reflection in daily work. Our findings are also consistent with the findings of Hurteau et al ( 2020 ) that the development of intuition is fostered by expertise and experiences. Also consistent with the findings of Kvande et al ( 2016 ), our study emphasizes the importance of being physically present with a patient to develop the clinical gaze.…”
Section: Discussionsupporting
confidence: 93%
“…It is also the only subcode present in all interviews, suggesting First-Hand Experience is the predominant experiencebuilding practice among practitioners. This result aligns with the strong emphasis on experience as a contributor to expertise development described in the literature (Chi, 2006;Hurteau et al, 2020;Patel & Groen, 1991;Phillips et al, 2004;Seifert et al, 1997) and supports the framework depiction of Outcome feeding back into the intuition lightbulb.…”
Section: Experiencesupporting
confidence: 80%
“…Interestingly, the idea of "incorrect intuition" leading to failure did not emerge in any of the interviews; however, there was an implication that failures were the result of inexperience and underdeveloped intuition. The ability of success and failure (i.e., Outcome) to collectively develop intuition has been reported in the literature (Hurteau et al, 2020). LITES subsequently depicts Outcome feeding back into intuition to capture how Experience is built upon the Outcome of past problem-solving scenarios.…”
Section: Outcomementioning
confidence: 99%
“…Policymakers are frequently concerned about the impacts of their schemes as well as unforeseen unintended consequences. Hurteau et al (2020) point out that expert intuition is increasingly considered to be a valid form of knowledge. A trained expert can use intuition to verify the results of rational analysis as well as any alternate tools decision-making process.…”
Section: How Intuition Can Help Improve Administrative Decision-makingmentioning
confidence: 99%